Resolution of taxonomic problems associated with the complex publication history of the seminal Torre and Bartsch monograph on Cuban Urocoptidae (Gastropoda, Pulmonata) - Kabat, Alan R.; Hershler, Robert; González-Guillén, Adrian (Zootaxa, 2012)
This paper clarifies the confusion relating to the publication of Carlos de la Torre & Paul Bartsch’s taxonomic study of theCuban Urocoptidae. This massive work, which described >500 new taxa, was completed in manuscript form in 1943, butwas not published during the authors’ lifetime. In 1972 Miguel Jaume and Alfredo de la Torre (a nephew of C. de la Torre)published a slightly modified version of a large portion of this manuscript in the Circulares del Museo y Biblioteca deZoología de la Habana, a mimeographed journal which is available for taxonomic purposes per ICZN Code Article 8. The420 new taxa introduced in this paper were made available under the ICZN Code (even though many were differentiatedonly in identification keys) and should be attributed to C. de la Torre & Bartsch because the descriptions were copied fromthe 1943 manuscript and Jaume & A. de la Torre explicitly credited this work to the former two authors (per Article 50 ofthe 1964 edition of the ICZN Code). The 1972 paper does not delineate type material for most of the new species-grouptaxa; however the detailed information provided in the 1943 manuscript constitutes valid evidence of the type series perICZN Code (1999) Article 72.2. The 1972 paper was republished by Jaume & A. de la Torre in 1976 in the Ciencias Bi-ológicas of the Universidad de la Habana. In 1980 Jaume & A. de la Torre prepared a typescript describing the remainingnew taxa from the 1943 manuscript, which was slated to be published in the Circulares; however we have not found anyevidence that it was distributed or otherwise made available in a manner satisfying the ICZN Code criteria for availability.In 2008 Carolina de la Torre, grand-niece of C. de la Torre, published the entire 1943 manuscript in a book of more than760 pages that was printed in Havana. The authorship of this book was credited to C. de la Torre & Bartsch. The bookdescribes as new the taxa already treated in the 1972 paper as well as 130 additional taxa, which also should be attributedto C. de la Torre & Bartsch. We briefly discuss the disposition of the Cuban urocoptid material studied by C. de la Torre & Bartsch and the subsequent citations to their taxonomic study of this fauna.